Pulmonary toxicity in a rabbit model of stereotactic lung radiation therapy: Efficacy of a radioprotector. (3rd July 2014) - Mata, Jaime; Sheng, Ke; Hagspiel, Klaus; Ruppert, Kai; Sylvester, Peter; Mugler, John; Fernandes, Carolina; Guan, Steven; Larner, James; Read, Paul
ABSTRACT: This study aimed to assess the efficacy of the radioprotector amifostine in limiting radiation toxicity in a rabbit model of lung stereotactic body radiation therapy (SBRT) by correlating contrast-enhanced magnetic resonance angiography (ce-MRA), computed tomography (CT), and helium-3 (He-3) magnetic resonance imaging (MRI) with histopathology. Multiple MRI techniques were tested to obtain complementing physiologic information. Thirteen rabbits received SBRT to the right lower lobe of the lung. Specifically, 4 received 3 × 11 Gray (Gy), 6 received 3 × 11 Gy and 50 mg/kg of amifostine pre-SRBT, and 3 received 3 × 7, 3 × 9, or 3 × 13 Gy. Imaging was performed at baseline and 4, 8, 12, and 16 weeks post-SBRT. Ce-MRA perfusion difference between lungs in the irradiated group at 16 weeks post-treatment was statistically significant ( P = .04) whereas the difference in the irradiated + amifostine group was not ( P = .30). Histologically observed low red blood cell (RBC) count and CT hypodensity suggests changes were primarily related to perfusion; however, structural changes, such as increased alveolar size, were also present. No changes in He-3 MRI lung ventilation were observed in either group. Although radiation-induced injury detected in rabbits as CT hypodensity contrasted with increased density observed in humans/rodents, the changes in ce-MRA and CT were still significantly reduced after the addition of amifostine to SBRT. Use of CT and selected MRI techniques helped to pinpoint primary physiologic changes.